Digital Evolution: A Comparative Study on Implementing Workflow Management at Dadang Maranatha Photography - Banjarnahor, Wiwin; Sinuraya, Junus; Azanuddin; Purba, Bister; Tumanggor, Orli (Cattleya Darmaya Fortuna, 2024)
In the current digital era, photography companies still rely on manual task assignments to manage their daily operations. This process involves the use of physical notes, spreadsheets, and face-to-face communication to assign and monitor tasks for team members. Photographers, editors, and other staff receive instructions verbally or through text messages, often leading to ambiguity regarding priorities and deadlines. Project management aspects such as scheduling, resource allocation, and overall photography project assignments tend to lack structure. This research proposes the use of a notification-based workflow management system to address these challenges. By automating task assignments, monitoring, and team coordination through real-time notifications, photography companies can improve operational efficiency and enhance team productivity. This study provides insights into how technology integration can enhance photography project management and contribute to the development of more structured and efficient systems in the future.